Plasma fetuin‐A is associated with endothelial dysfunction and subclinical atherosclerosis in subjects with nonalcoholic fatty liver disease. (10th April 2013) - Dogru, Teoman; Genc, Halil; Tapan, Serkan; Aslan, Fatih; Ercin, Cemal Nuri; Ors, Fatih; Kara, Muammer; Sertoglu, Erdim; Karslioglu, Yildirim; Bagci, Sait; Kurt, İsmail and Sonmez, Alper
Abstract Objective Nonalcoholic fatty liver disease (NAFLD), a hepatic manifestation of metabolic syndrome (MetS) is closely associated with an increased risk of cardiovascular disease. Fetuin‐A is associated with MetS and NAFLD. We investigated the relationship of circulating fetuin‐A level with markers of endothelial dysfunction and presence of carotid atherosclerosis in subjects with NAFLD. Methods The consecutive 115 patients with NAFLD and age‐matched 74 healthy subjects were enrolled. Plasma levels of fetuin‐A and markers of endothelial dysfunction [asymmetric dimethyl arginine (ADMA) and adiponectin] were measured by ELISA method. Insulin sensitivity was determined by homeostasis model assessment of insulin resistance (HOMA‐IR) index. Carotid artery intima‐media thickness (cIMT) was assessed by high‐resolution ultrasonography. Results Fetuin‐A and ADMA were higher and, adiponectin was lower in NAFLD group than the control group (P = 0·004, P < 0·001 and P < 0·001, respectively). In addition, NAFLD group had greater cIMT measurements than the controls (P < 0·001). However, no difference was found for fetuin‐A, ADMA, adiponectin and cIMT between two groups when the findings were adjusted according to the glucose, lipids and HOMA‐IR index. In correlation analysis, fetuin‐A was found to be positively correlated with triglyceride (r = 0·23, P = 0·001), HOMA‐IR (r = 0·29, P < 0·001), ADMA (r = 0·24, P = 0·001), cIMT (r = 0·3, P = 0·003) and, negatively correlated with HDL‐C (r = −0·17, P = 0·02) and adiponectin (r = −0·19, P = 0·01) levels. Multiple linear regression analysis showed that fetuin‐A was independently associated with ADMA and cIMT levels. Conclusion This study demonstrated for the first time that circulating fetuin‐A in NAFLD is independently associated with endothelial dysfunction and subclinical atherosclerosis.